The relationship between multidimensional psychological well-being and poverty - Oaker, Brandon (School of Economics, 2020)
Evidence from various academic fields indicates that mental health and income are correlated. Additionally, evidence exists that an increase in income improves psychological well-being and evidence that poor psychological well-being negatively impacts income. The difficulty is that there is no definitive work pinpointing the direction of the causal relationship between income and psychological well-being, but studies are attempting to find out. Hence, this paper attempts to contribute to ongoing work with an IV estimation approach to determine the causal effects of psychological well-being on poverty. Using data provided by Haushofer and Shapiro, this paper finds evidence that an increase in income causes a reduction in depression and stress levels, along with increases in happiness and life satisfaction of the study participants. Additionally, it is found that these improvements in psychological well-being lead to increases in monthly household expenditure, especially health care. Furthermore, these findings indicate that when women receive a cash transfer, a significant proportion of that transfer is devoted to health care. All the estimates presented in the paper indicate that an improvement in economic well-being leads to an improvement in the mental health of the poor, which causes them to spend more and focus more on their health care.